Motivation as a mediator of the effect of job satisfaction on employee performance - Mister Candera; Pitri Yani; Edy Liswani (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2022)
The formulation of the problem in this study are (1) Is there any influence of Job Satisfaction on Employee Job Motivation at PT Kirana Permata Muara Enim, (2) Is there any influence of Job Satisfaction on Employee Performance at PT Kirana Permata Muara Enim, (3) Is there an Effect of Job Satisfaction on Performance Employees With Motivation as Mediation Variables at PT Kirana Permata Muara Enim. The objectives of this study are (1) To find out the Effect of Job Satisfaction on Employee Motivation at PT Kirana Permata Muara Enim, (2) To determine the Effect of Job Satisfaction on Employee Performance at PT Kirana Permata Muara Enim, (3) To find out the Effect of Job Satisfaction Towards Employee Performance With Motivation as a Mediation Variable at PT Kirana Permata Muara Enim. The type of research used is associative research, this study uses variables of job satisfaction, work motivation, and employee performance using 10 indicators. The population in this study were all employees at PT Kirana Permata Muara Enim, amounting to 356 employees. In this study, samples were taken from as many as 155 respondents with the area sampling method (cluster) sampling. The data used in this study are primary data. The data collection method used in this study is the postal questionnaire method. The data analysis used is qualitative, which is quantitative by using the path analysis technique. The results showed that (1) there was a significant influence of job satisfaction on employee motivation at PT Kirana Permata Muara Enim, (2) there was a significant effect of job satisfaction on employee performance at PT Kirana Permata Muara Enim, (3) there was a significant influence of job satisfaction on employee performance with motivation as mediating variable PT Kirana Permata Muara Enim